2018
DOI: 10.1088/1748-0221/13/03/c03031
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared scintillation of liquid argon: recent results obtained with the NIR facility at Fermilab

Abstract: After a short review of previous attempts to observe and measure the near-infrared scintillation in liquid argon, we present new results obtained with NIR, a dedicated cryostat at the Fermilab Proton Assembly Building (PAB). The new results give confidence that the nearinfrared light can be used as the much needed light signal in large liquid argon time projection chambers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…The present results are also in compliance with those of [11,13] (FNAL group): light emission in the NIR in liquid Ar were observed there in the range of 715-900 nm, when irradiated with 511 keV gamma-rays and 5.4 MeV alpha particles. Analyzing the pulse shapes presented in [11], one may conclude that the authors observed the fast (𝜏 𝑓 < 100 ns) and slow (𝜏 𝑠 = 2-4 μs) signal components, similarly to that of the present work.…”
Section: Comparison With the Previous Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The present results are also in compliance with those of [11,13] (FNAL group): light emission in the NIR in liquid Ar were observed there in the range of 715-900 nm, when irradiated with 511 keV gamma-rays and 5.4 MeV alpha particles. Analyzing the pulse shapes presented in [11], one may conclude that the authors observed the fast (𝜏 𝑓 < 100 ns) and slow (𝜏 𝑠 = 2-4 μs) signal components, similarly to that of the present work.…”
Section: Comparison With the Previous Resultssupporting
confidence: 92%
“…On the other hand, there were indications on light emission in the visible and near infrared (NIR) range in liquid Ar in S1 signal [6][7][8][9][10][11][12][13][14], albeit at a much lower yield, of the order of 500 photon/MeV [6], the origin of which is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The present results are also in compliance with those of [11,13] (FNAL group): primary scintillations in the NIR in liquid Ar were observed there in the range of 715-900 nm, when irradiated with 511 keV gamma-rays and 5.4 MeV alpha particles. Analyzing the pulse shapes presented in [11], one may conclude that the authors observed the fast (𝜏 𝑓 < 100 ns) and slow (𝜏 𝑠 = 2 − 4 𝜇s) signal components, similarly to that of the present work.…”
Section: Comparison With the Previous Resultssupporting
confidence: 92%
“…On the other hand, there were indications on the production of primary scintillations in the visible and near infrared (NIR) range in liquid Ar [6][7][8][9][10][11][12][13][14], albeit at a much lower yield, of the order of 500 photon/MeV [6], the origin of which is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the total number of quanta is higher than assumed here, due to W being lower, as recently measured by EXO-200, 11.5 ± 0.5 eV [110] as opposed to 13.7 ± 0.2 eV (Dahl [36]) or 13.4 ± 0.4 eV (Goetzke, neriX [65]) or 13.8 ± 0.9 eV (Doke [78]), then this basement is unlikely to change significantly, as even F q = 0 was explored above. This discrepancy, observed in the light not charge channel and thus unlikely to be due to charge amp calibration differences, may be due to SiPMs being more sensitive (relative to PMTs) to wavelengths other than VUV, such as infrared (IR scintillation has been observed in LAr [116]). While at 2 nd order the fluctuation models in NEST would have to be revised, to 1 st order everything discussed here would remain the same, but with g 1 and g 2 estimates decreasing by ∼15%.…”
Section: High Energy: the Mev Scale (Neutrinoless Double-beta Decay)mentioning
confidence: 99%